Analisis Kinerja Industri Kakao di Indonesia: Pendekatan Structure-Conduct-Performance (SCP) - Shafira Ayu Amalia; Firmansyah Firmansyah (Journal of Economics and Business, 2021)
This research employs the Structure-Conduct-Performance (SCP) paradigm to analyze the structure, conduct, and performance of cocoa industry in Indonesia during 2012-2014 period. Concentration ratio of the four largest companies (CR4) and minimum efficiency of scale (MES) is used as an indicator of market structure of the cocoa industry. The conduct of cocoa industry is explained by capital-labor ratio (CLR). While the performance of cocoa industry is seen from price-cost margin (PCM), internal efficiency (XEF) and output growth (Growth). This research uses panel data to see the effect of market share (MS), capital-labor ratio, internal efficiency, and output growth on price-cost margin. The results of this research shows that the structure of cocoa industry in Indonesia is very high tight oligopoly, with a high entry barrier. This is seen from the value of CR4 and MES which are bigger than 60 percent each year. Furthermore, cocoa industry can be classified as capital intensive industry. This is seen from the high value of CLR. Based of the regression results using random effect model (REM), market share has a negative significant effect on the price cost margin. While capital-labor ratio, internal efficiency, and output growth have a positive significant effect on the price-cost margin.